The use of religious symbols in local brand advertisement as objects of trade / Mohd Fauzi Harun, Prof Madya Dr. Halim Husain and Dr. Nur Safinas Albakry - Mohd Fauzi, Harun; Halim, Husain; Nur Safinas, Albakry (Universiti Teknologi MARA, Perak, 2018)
Good advertisements always tend to have the eye-catching elements and have to be memorable for the viewer. The cut-throat competitive market environment has made the advertising field explode with different marketing techniques and ideas not just to inform but transform the viewer’s belief, in other words to influence people. Each of these advertisements has uniqueness to state. Starting by selecting the right words, images, symbols, format and tone are examples of common measures for the message that later transform these content of a message (thought, ideas etc.) into a symbolic form of encoding by the viewer. Selection of visual communication design is more than just a nonverbal communication. In any advertisement, it is a study that combined design, cognitive psychology and semiology in response to the highly developed commercial society. Unfortunately, these visual communication designs are implied with hidden messages and influences that later affects viewer actions and thoughts. Selling Islamic value or called so Islamic ‘look like’ ads is one of the hard sell marketing communications in getting trust easily for the Muslim consumer where the religious notion presented as objects of trade, a commodity where else the product as main subject is denied. The aim of this paper is to reveal in comprehensive the religious commodification through advertisement specifically by Malaysian local brands. The main data of the research is billboard advertisement advertised by local brands as the main documentation. A content analysis is used to analyze all documented billboards using Semiotic analysis other than literature study. The result of the study shows the existence of representative form of Islam, and is being exploited as commodities to be traded in most parts of the ads. These symbols are combined as one of the commercial element, manipulated and designed mostly through the use of words, phrases, and images. The adaptation of Islamic values will represent nothing for some whilst it can lead to the elements of fraud and misleading especially in a Multi-religion country. The words or visual used might slightly differ in meaning which may cause confusion.